2011
DOI: 10.1071/ch10293
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence Quenching of Quantum Dots by DNA Nucleotides and Amino Acids

Abstract: Quantum dots found widespread application in the biosciences as bright and highly photo-stable fluorescent probes, i.e. for single-particle tracking. In this work we used ensemble spectroscopy and single-molecule techniques to study the quenching of quantum dots by various biochemical compounds that are usually present in living cells and might thus influence the experiments. We found not only nucleotides such as cytosine, guanine, and thymine can significantly influence the fluorescence emission of CdSe and C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 30 publications
1
19
0
Order By: Relevance
“…It is unlikely that the observed significant quenching of the PL was caused by aggregate formation, which usually causes spectral broadening or spectral shifts, since neither changes in the emission spectra nor shifts in the emission maxima of the QDs were observed (Figure 2b) in the presence of DNA 25, 26. Probably, electron transfer between QDs and nucleotide bases plays a major role, supported by the fact that DNA‐induced quenching was recently reported for cysteine‐capped QDs,11 which was attributed to electron transfer between QDs and nucleotide bases 11, 12. However, the exact mechanism of quenching is still elusive.…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…It is unlikely that the observed significant quenching of the PL was caused by aggregate formation, which usually causes spectral broadening or spectral shifts, since neither changes in the emission spectra nor shifts in the emission maxima of the QDs were observed (Figure 2b) in the presence of DNA 25, 26. Probably, electron transfer between QDs and nucleotide bases plays a major role, supported by the fact that DNA‐induced quenching was recently reported for cysteine‐capped QDs,11 which was attributed to electron transfer between QDs and nucleotide bases 11, 12. However, the exact mechanism of quenching is still elusive.…”
Section: Resultsmentioning
confidence: 82%
“…However, in such systems, labeling of nucleic acids is still necessary to investigate siRNA release. Recently, it has also been demonstrated that electron transfer between QDs and DNA induces QD emission quenching,11, 12 which is attractive for the development of label‐free DNA detection and delivery systems.…”
Section: Introductionmentioning
confidence: 99%
“…For this, we first assessed if the interaction with proteins will have any effect on the fluorescence properties of carbon dots. Interactions such as those with intracellular proteins have been observed to effect the fluorescence properties of various organic fluorophores and quantum dots . We monitored the fluorescence emission of carbon dots in Bovine serum albumin solution (4 mg/mL in phosphate buffer saline) at various pH over 12 hours.…”
Section: Methodsmentioning
confidence: 99%
“…concluded that nucleotides were not suitable stabilizers for these materials . A later study by Siegberg and Herten reported that nucleotide monophosphates quench quantum dot fluorescence upon adsorption, though stability studies were not performed …”
Section: Applications Of Nucleotide‐containing Cpsmentioning
confidence: 99%